Transient Interaction of a Spherical Shell with an Underwater Explosion Shock Wave and Subsequent Pulsating Bubble - H. Huang; K.C. Kiddy (Shock and Vibration)
The nonlinear interaction problem is analyzed by simultaneously solving the mass, momentum, and energy conservation equations together .with appropriate material constitutive equations governing the fluid dynamics of the explosion gaseous product and the water and the structural dynamics of the compliant shell. A finite difference technique in a coupled Eulerian–Lagrangian scheme is used. The computer program PISCES 2DELK is employed to carry out the numerical computations. The results demonstrate that to rigorously analyze the response of a submerged structure to a nearby explosion, the interactions among the explosion shock wave, the structure, its surrounding media, and the explosion bubble need to be considered.